Serum selenium and reduced mortality in middle-aged and older adults with prefrailty or frailty: the mediating role of inflammatory status - Chang, Chih-Po; You, Ching-Hui (Frontiers in Nutrition, 2025)
BackgroundFrailty is associated with increased mortality risk among middle-aged and older adults. Selenium, a trace element with antioxidant properties, may play a role in reducing mortality by modulating inflammatory processes. This study aimed to investigate the association between serum selenium and mortality in individuals with prefrailty or frailty, with a specific focus on potential mediators.MethodsData of participants of National Health and Nutrition Examination Survey (1988–1994 and 2011–2016) of the US, aged 40–79 years with serum selenium measurements and frailty-related assessments were analyzed. All-cause and cardiovascular disease (CVD) mortality were confirmed by the National Death Index death certificate data. Systematic inflammation status was surrogated by the systemic immune inflammation index. Multivariable Cox proportional hazards models, restricted cubic spline (RCS) analysis, and mediation analysis were used to assess the associations.ResultsAmong 1,454 participants, those in the second, third, and fourth quartiles of serum selenium had significantly lower risks of all-cause mortality compared to the lowest quartile. The highest selenium quartile also showed a reduced risk of cardiovascular disease (CVD) mortality. Non-linear analysis indicated a significant relationship between selenium levels and all-cause mortality. Mediation analysis did not reveal that the protective effects of selenium were mediated by, CVD, chronic kidney disease, diabetes mellitus, or systemic inflammation status [as surrogated by the systemic immune-inflammation index (SII)].ConclusionHigher serum selenium levels are linked to a lower risk of all-cause and CVD mortality in individuals with prefrailty or frailty. These findings highlight the need for future studies to clarify the pathways through which selenium may reduce mortality in prefrail and frail populations, and to determine whether selenium supplementation could offer therapeutic benefits.